Greenhouse Gas Emissions From Arctic Lakes And Ponds As Influenced By Carbon Lability. - Préskienis, Vilmantas; Bouchard, Frédéric; Laurion, Isabelle; Fortier, Daniel (2014)
The rapid climate warming in Arctic regions has induced extensive permafrost thawing and the consequent mobilization of a large reservoir of organic carbon that was frozen for millennia. Although the release of this old carbon into the atmosphere, either as carbon dioxide (CO2) or methane (CH4), acts as a positive feedback mechanism to global warming, very little is known about the extent and rate of the gas release and the biochemical processes involved as the different carbon pools are becoming available to ecosystems of Arctic lakes and ponds. As a part of an interdisciplinary project investigating the influence of geomorphological and limnological factors on GHG emissions from lakes and ponds on Bylot Island, Nunavut, the present study aims to determine the lability and accessibility of the different carbon pools to microorganisms. In 2014, lability experiments were performed on four sediment types found in organic-rich polygonal patterned ground landscape and possessing specific characteristics (e.g., annual thermal regime, C/N ratio): upper-half portion of the active layer, lower-half of the active layer, permafrost, and thermokarst lake sediment. The different soil samples were incubated in-situ in shaded conditions, in one of the shallow tundra ponds. These incubation tests were repeated in controlled and stable temperature conditions in laboratory. Leachates were also produced from the same soils and incubated similarly both in the field and in the laboratory. Dissolved oxygen (O2) and headspace CH4 and CO2 concentrations were measured regularly over a period of up to two weeks, and the rates of consumption or production were calculated. Preliminary results show that O2 consumption rates were higher in upper active layer samples, while it depleted more slowly in other incubations, suggesting the presence of active aerobic consumers of organic matter in active layer soils naturally exposed to O2. On the other hand, the production of CO2 was faster in lake sediments, whereas permafrost soils showed ...